Layered TMDFETS for Nano Devices: A Short Review - Dhar, Subhra; Pattanaik, Manisha (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2019)
Two-dimensional semiconducting materials of the transition-metal-dichalcogenide (TMD) family, such as MoS\({}_{2}\) and WSe\({}_{2}\), have been intensively investigated in the past few years, and are considered as workable contenders for next-generation electronic devices. In this very brief review, we provide an evaluation of devices based on monolayer and multi layer two-dimensional materials, outlining their prospects as a technological option for low power transistor designs. Our study revealed that the two dimensional transition-metal-dichalcogenide are versatile materials which may be used as a single layer or multi layered with diverse properties enabling to suit a wide range of low power applications. Further study divulges that experimental investigations of monolayer TMD transistors encourage workers with excellent carrier mobilities required for low power applications, whereas multilayer TMD transistors reveal WS\({}_{2}\) to be an excellent channel material for making of high performance FET required for energy efficient electronic applications. We understand that this work will provide an important step towards the design and performance evaluation of FETs in low power applications based on two-dimensional materials. Further, the results obtained due to the TMDs so far, prove beneficial to both states of FET operation i.e. ON state and OFF state, when compared to conventional materials.